Study of Population and Diversity of Diurnal Avifauna in Coban ‎Tarzan and Coban Kodok Malang-East Java: an Inspiration From Holy ‎Qur’an - Ahmad‎, Mujahidin; Hanifa, Berry ‎ Fakhry; Mulyono, Rizky Mujahidin; Abidin, Mohammad ‎ Ahlim Ihsan; Pranata, Yudha Setya (El-Hayah : Jurnal Biologi, 2020)
Birds are a very important part of biodiversity. Birds can also be used as indicators of environmental quality because bird diversity is also related to ecosystem balance. This study aims to determine the population and diversity of diurnal birds in Coban Tarzan and Coban Kodok in Malang Regency. The data explained that 17 species of birds found in Coban Tarzan and 17 species of birds also in Coban Kodok respectively. Then the Diversity, Evenness, and Dominance index in Coban Kodok were 2,25; 0.85; 0,15 repectivelty. while in Coban Tarzan were 2,13; 0.83; 0,17 respectively. Overall, Coban Kodok has better values of diversity and both of location have no significant different of evenness and dominance index